STRATEGIES TO SOLVE WRITING DIFFICULTIES ON RECOUNT TEXT FOR JUNIOR HIGH SCHOOL IN SMP NEGERI 8 PEMATANG SIANTAR - DANIEL MARTIN MARBUN; LISBET AGUSTINA OPPUSUNGGU; THALITHA VICTORYA PARDEDE; JESSICA NATALIA TAMPUBOLON (CV KULTURA DIGITAL MEDIA, 2022)
The purpose of this study is to learn about the teachers’ strategies to help students overcome their problems in creating recount texts. This research was carried out in SMP Negeri 8 Pematang siantar eighth-grade. The study is part of a qualitative investigation. Two English teachers were among the participants in this research. Interviews with two English instructors at Junior High School were conducted as part of the research inquiry. Interviewing and recording were used to acquire data. To analyze the data, there were various steps: first, analyzing the students' issues, then interviewing the teachers, and last, descriptive analysis. The study's findings show that the teachers' strategies for overcoming difficulties are as follows: (a) in content, the teachers used picture series as learning media and guided writing; (b) in organization, the teachers used guided writing; (c) in grammar, the teachers used random words, text modeling, and mini dictionary products; (d) in mechanics, the teachers recommended that students improve their reading habits; (e) in generic structure of rec, the teachers recommended that students improve their reading habits; (f) in generic structure of recount text aspect, the teachers used semi guided and supported by picture series as learning media.